Frequency-Domain Analysis of a Single-Machine Infinite-Bus Control System Equipped with a Power System Stabilizer Using the Backtracking Search Algorithm - Laksono, Heru Dibyo; Salim, Suci Maretta (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
The SMIB model with a PSS optimized through the BSA is employed in this research to investigate the improvement of electrical power system stability. The performance of both open-loop and closed-loop systems is evaluated through frequency domain analysis. System stability and control efficacy are evaluated through key metrics such as gain and phase margins, resonance peaks, and robustness parameters. Simulation outcomes reveal marked enhancements in the optimized configuration. In particular, the phase margin is negative, suggesting instability, and the open-loop gain margin is infinite in the absence of PSS. The introduction of the BSA-optimized PSS leads to a gain margin of 27.96 dB and an infinite phase margin, which satisfy the design specifications. The closed-loop bandwidth surpasses 7.11 rad/s, with the resonance peak maintained between 1.0 and 1.5, allowing for prompt transient response and robust performance. This study underscores BSA's effectiveness in fine-tuning PSS parameters, yielding enhanced system stability and attenuation of low-frequency oscillations. These results contribute to the development of advanced robust control methodologies in power systems.